2020
DOI: 10.1371/journal.pone.0227182
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial profiles of physical activity fluctuation in office employees: A latent profile analysis

Abstract: Objectives Fluctuation is a common but neglected phenomenon of physical activity (PA) behavior. This study aimed to explore the psychosocial profiles of PA fluctuation in office employees, and to examine the association of latent profiles with demographics and PA level. Method 434 Chinese office employees who were identified as PA fluctuators (M = 32.4 years, SD = 6.9, 55.5% female) completed a cross-sectional online survey covering demographics, PA behavior, and six psychosocial indicators (self-efficacy, pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 43 publications
1
13
0
3
Order By: Relevance
“…Furthermore, entropy was also reported only to demonstrate the precision with which the cases were classified in the profiles (on a 0 to 1 scale). However, entropy does not serve as a main indicator by which to determine the optimal number of profiles [26]. In the case of the categorical and continuous variables, BIC and CAIC could correctly identify the correct class model close to 100% of the time [27].…”
Section: Goodness Of Fit and Description Of Latent Classesmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, entropy was also reported only to demonstrate the precision with which the cases were classified in the profiles (on a 0 to 1 scale). However, entropy does not serve as a main indicator by which to determine the optimal number of profiles [26]. In the case of the categorical and continuous variables, BIC and CAIC could correctly identify the correct class model close to 100% of the time [27].…”
Section: Goodness Of Fit and Description Of Latent Classesmentioning
confidence: 97%
“…As illustrated in Table 2, the seven-class model was the best fit, representing an adequate solution for the data because it had the lowest BIC and CAIC values. However, accuracy decreased as the sample size increased, which is a known problem with AIC because there is no adjustment for sample size [26]. Furthermore, entropy was also reported only to demonstrate the precision with which the cases were classified in the profiles (on a 0 to 1 scale).…”
Section: Goodness Of Fit and Description Of Latent Classesmentioning
confidence: 99%
“…This group of persons is referred to as "fluctuators, " and their fluctuating PA behavioral pattern is referred to as "fluctuation" (Shang et al, 2018;Duan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a recent study of fluctuators' psychosocial profiles discovered that fluctuators' mindsets might be variable. Their commitment to PA involvement differed significantly according to their demographic characteristics, such as employment position and weight status (Duan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that the presence of social support may have a positive effect on the frequency of PA [14,15]. As such, group PA sessions and use of exercise facilities, parks, and trails for exercise are increasing in popularity.…”
Section: Introductionmentioning
confidence: 99%